The Spanish Latin lover: a strictly domestic myth? - Alicia Fuentes Vega (Via@)
The character of the Mediterranean Latin lover became increasingly popular in late-Francoism Spain owing to a subgenre of films that exploited masculine phantasies of sexual encounters with foreign tourists. Building on a visual analysis of several media (brochures and magazines, Government propaganda, guidebooks and travel books, postcards), this paper examines the actual presence of the Latin lover in Spanish tourism imaginaries during the Franco dictatorship. Despite its important role in the hegemonic narrative of Spain’s tourism boom as a liberalizing factor that clashed against the regime, the myth of the Spanish Don Juan remains absent from the destination image intended for foreign audiences. This suggests that its circulation was strictly domestic, and reinforces its interpretation as a governmentality device.